Pengetahuan Literasi Jasmani Pada Siswa Kelas X SMAN Kalisat - Guruh Permadi Yoga Saputra; Riski Apriliyanto; Bahtiar Hari Hardovi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to provide a comprehensive picture of the physical literacy knowledge of class X students at SMAN Kalisat Jember. Measurement of physical literacy understanding using 9 items of the "perceived physical literacy instrument" (PPLI) which has been validated by previous researchers with a validation level of 0.82 (very good). Data collection using a questionnaire based on the PPLI instrument and given to 74 class X students of SMAN Kalisat. The results of the study also showed that out of 9 questionnaire items, there were 8 hesitant answers to the understanding of physical literacy, namely P1, P3, P4, P5, P6, P7, P8 and P9. This shows that some of the class X students of SMAN Kalisat are still hesitant, especially in category P5 with a percentage of 52.60% and for all statements, the answers agree and strongly agree were all answered with different percentages. Category P1 is in the top position with a percentage of 69.45% for agree answers, and for strongly agree answers in the top position with a percentage of 52.48%, namely P2. The conclusion that can be drawn from this study is that students have actively participated in physical activities and understand the benefits of physical activities, and students have self-confidence related to physical activities. Keywords: Physical Literacy, Physical Education, Knowledge